2019
DOI: 10.1002/mrd.23228
|View full text |Cite
|
Sign up to set email alerts
|

TP53BP1 regulates chromosome alignment and spindle bipolarity in mouse oocytes

Abstract: Meiotic oocytes lack classic centrosomes; therefore, bipolar spindle assembly depends on the clustering of acentriolar microtubule‐organizing centers (MTOCs) into two poles. The bipolar spindle is an essential cellular component that ensures accurate chromosome segregation during anaphase. If the spindle does not form properly, it can result in aneuploidy or cell death. However, the molecular mechanism by which the bipolar spindle is established is not yet fully understood. Tumor suppressor p53‐binding protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…Tumor suppressor p53 binding protein 1 (Trp53bp1) plays a role in maintaining the bipolar spindle during mitosis (Lambrus et al 2016). Recent studies have revealed that Trp53bp1 knockdown affects spindle bipolarity and chromatin alignment by altering MTOC stability during oocyte maturation (Jin et al 2019). In our present study, we also found abnormal splicing of Rac1, which has previously been shown to contribute to spindle positioning and oocyte cortical polarity during mouse oocyte meiosis (Halet and Carroll 2007).…”
Section: Discussionsupporting
confidence: 73%
“…Tumor suppressor p53 binding protein 1 (Trp53bp1) plays a role in maintaining the bipolar spindle during mitosis (Lambrus et al 2016). Recent studies have revealed that Trp53bp1 knockdown affects spindle bipolarity and chromatin alignment by altering MTOC stability during oocyte maturation (Jin et al 2019). In our present study, we also found abnormal splicing of Rac1, which has previously been shown to contribute to spindle positioning and oocyte cortical polarity during mouse oocyte meiosis (Halet and Carroll 2007).…”
Section: Discussionsupporting
confidence: 73%
“…PMS1, MLH1, and MSH2 are likely to form a ternary complex during the initiation of eukaryotic DNA mismatch repair (Prolla et al, 1994). Numerous researches have revealed that tumor suppressor p53-binding protein 1 (TP53BP1) is a central transducer of DNA-damage signals to p53, may work together in the p53-mediated transcriptional activation and DNA damage-repair signaling pathways (Ma et al, 2006), plays an essential role in the cellular response to DNA damage, chromosome stability and spindle bipolarity during meiotic maturation (Jin et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Another DSB repair protein, the tumor suppressor p53-binding protein 1 (TP53BP1), also seems to affect spindle formation. RNAi for TP53BP1 impairs oocyte maturation by destabilizing microtubule organizing centers (MTOC) which causes the formation of nonbipolar spindles and chromosome misalignment [ 61 ].…”
Section: Physiological Role Of Ddr Components In Oocytesmentioning
confidence: 99%